Selenoprotein P Modulates Methamphetamine Enhancement of Vesicular Dopamine Release in Mouse Nucleus Accumbens Via Dopamine D2 Receptors - Torres, Daniel J.; Yorgason, Jordan T.; Mitchell, Catherine C.; Hagiwara, Ayaka; Andres, Marilou A.; Kurokawa, Suguru; Steffensen, Scott C.; Bellinger, Frederick P. (Frontiers in Neuroscience, 2021)
Dopamine (DA) transmission plays a critical role in processing rewarding and pleasurable stimuli. Increased synaptic DA release in the nucleus accumbens (NAc) is a central component of the physiological effects of drugs of abuse. The essential trace element selenium mitigates methamphetamine-induced neurotoxicity. Selenium can also alter DA production and turnover. However, studies have not directly addressed the role of selenium in DA neurotransmission. Selenoprotein P (SELENOP1) requires selenium for synthesis and transports selenium to the brain, in addition to performing other functions. We investigated whether SELENOP1 directly impacts 1) DA signaling and 2) dopaminergic response to methamphetamine. We used fast-scan cyclic voltammetry to investigate DA transmission and the response to methamphetamine in NAc slices from C57/BL6J SELENOP1 KO mice. Recordings from SELENOP1 KO mouse slices revealed reduced levels of evoked DA release and slower DA uptake rates. Methamphetamine caused a dramatic increase in vesicular DA release in SELENOP1 KO mice not observed in wild-type controls. This elevated response was attenuated by SELENOP1 application through a selenium-independent mechanism involving SELENOP1-apolipoprotein E receptor 2 (ApoER2) interaction to promote dopamine D2 receptor (D2R) function. In wild-type mice, increased vesicular DA release in response to methamphetamine was revealed by blocking D2R activation, indicating that the receptor suppresses the methamphetamine-induced vesicular increase. Our data provide evidence of a direct physiological role for SELENOP1 in the dopaminergic response to methamphetamine and suggest a signaling role for the protein in DA transmission.